Updated magnetized transport coefficients: impact on laser-plasmas with self-generated or applied magnetic fields. (30th September 2021) - Walsh, C.A.; Sadler, J.D.; Davies, J.R.
Abstract: Errors in the Epperlein and Haines (1986 Phys. Fluids ) transport coefficients were recently found at low electron magnetizations, with new magnetic transport coefficients proposed simultaneously by two teams (Sadler et al 2021 Phys. Rev. Lett. and Davies et al 2021 Phys. Plasmas ); these two separate sets of updated coefficients are shown in this paper to be in agreement. The importance of these new coefficients in laser-plasmas with either self-generated or applied magnetic fields is demonstrated. When an external magnetic field is applied, the cross-gradient-Nernst term twists the field structure; this twisting is reduced by the new coefficients in the low magnetization regime. For plasmas where only self-generated magnetic fields are present, the new coefficients are found to result in the magnetic field moving with the Righi–Leduc heat-flow, enhancing the impact of MHD. Simulations of Biermann battery magnetic fields around ICF hot-spot perturbations are presented, with cross-gradient-Nernst transport increasing spike penetration.